EXAMINING THE ROLE OF MARKETING COMMUNICATION, AND BRAND EXPERIENCE ON BRAND LOYALTY: THE MEDIATIONAL ROLE OF BRAND LOVE - Muhammad Awais Bhatti; Khaled Mohammed Ahmed Alqasa (Fonseca, Journal of Communication, 2024)
In today’s competitive landscape, organisations must prioritise customer retention to ensure longterm success. Identifying the factors that facilitate the development of emotional connections with consumers is crucial. This study examines the impact of marketing communication, brand credibility, and brand experience on brand love and brand loyalty. A cross-sectional research design was employed to investigate these relationships. Data was collected by distributing a questionnaire to customers of telecom sector companies in KSA. The questionnaire utilised a Likert scale format and was distributed to customers through a simple random sampling method, achieving a response rate of 72.67%. Smart PLS was used as the analysis tool for this research. The findings revealed that brand credibility, brand experience, and brand love profoundly influence customer loyalty. Additionally, brand experience and marketing communication are critical in shaping brand love. The study offers a thorough analysis of both theoretical and practical implications